Interdisciplinary environmental studies : a primer - Oberg, Gunilla (Chichester : Wiley-Blackwell, 2011)
'Interdisciplinary work is to a large extent a question of entering the unknown, an adventure with exciting and endless opportunities'--
Includes bibliographical references and index.
Keywords: Interdisciplinary research